Mapping social exclusion in India : caste, religion and borderlands - Judge, Paramjit S. (Cambridge, Cambridge University Press, 2014)
"Identifies and examines various trajectories of exclusion at both macro and micro levels in India"--
Includes bibliographical references and index.
Keywords: Marginality, Social -- India; Marginality, Social -- Religious aspects; Caste -- India; Social stratification -- India